(untitled) (The Nepali Mathematical Sciences Report, 2025)
Graphical reasoning plays a crucial role in helping students grasp mathematical ideas, particularly those involving functions, calculus, and their applications in science. Yet in Nepal, this aspect of mathematics education is widely underdeveloped. This article analyzes the current situation in Nepal’s high school mathematics system, examining how curriculum, teaching practices, and assessments neglect graphical learning. Drawing on research, observations, and comparative insights, it highlights the systemic issues that undermine students’ conceptual understanding and proposes practical steps to bring about reform. The article makes the case for a stronger emphasis on visual reasoning, supported by thoughtful curriculum design, better teacher preparation, appropriate use of technology, and meaningful testing.